Assesing Economic Factors Influencing Selection of Sanitation Technologies in Kapseret Subcounty, Uasin Gishu County, Kenya - JEBET, MERCY; Kubai, Patrtick; Muthuri, Grace (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Background: Assessment the economic factors influencing choice of sanitation technologies for improved sanitation services is necessary not only in Kenya but in most low and middle income countries. This study explored the lived experiences of residents in Kapseret Sub County, Uasin Gishu County, Kenya. It analysed the social and economic factors influencing household decisions on sanitation technologies. Methodology: The study was conducted in Kapseret Sub County, Uasin Gishu County, Kenya, with a population of 198,499 and 59,746 households. The target sample was 475 households, calculated using the Yamane formula, and data was collected through questionnaires, observation checklists, and interviews. A cross- sectional descriptive study design incorporating both quantitative and qualitative methods was employed. Purposive and cluster sampling techniques were used to obtain appropriate sample size. From each cluster, simple random sampling technique was utilized to choose the respondents. Data analysis was conducted using SPSS Version 26 to generate descriptive and inferential statistics. Results: This study investigates sanitation choices within households. The majority of household leaders are men between 34 and 54, with families of 3-6 people. Most people live in rented, permanent structures, and have access to basic amenities like improved sanitation facilities (almost 69%) and piped water (over 73%). Interestingly, while most people deny that cultural beliefs directly impact their sanitation choices, traditional customs (40%) and gender roles (65%) seem to play a significant role. Financial constraints are a major concern for over 85% of respondents. There’s also a link between education and household situation - over 64% have higher education, and education level is connected to both family size and employment status. Finally, the study found a clear connection between the type of housing and the sanitation technology a household chooses. Recommendations: Implement community education programs on sanitation rights and practical solutions to empower residents. Address financial barriers to enable access to advanced sanitation technologies. Consider cultural norms and community attitudes in sanitation interventions. Conclusions: The study highlights the complex interplay between cultural norms, economic constraints, and practical factors in household sanitation technology choices. Education and financial support are crucial in fostering sustainable sanitation practices and improving health outcomes.